Invoking Precedent: Discussion of Supreme Court Decisions at Circuit Court Confirmation Hearings. Issue 3 (May 2020) - Dancey, Logan; Nelson, Kjersten; Ringsmuth, Eve M.; Solomon, Emma
Judicial confirmation hearings offer a rare opportunity for senators to engage in a public exchange with current and future members of the federal judiciary. Below the Supreme Court level, however, we know relatively little about how members of the Judiciary Committee use these hearings. In this article, we examine senator mentions of Supreme Court cases at circuit court confirmation hearings between 1993 and 2012 to test whether these hearings serve as a venue for position-taking, as well as for interbranch dialogue. We find evidence that senators do reference decisions in ways that seem motivated by electoral considerations. However, we also find that hearings are frequently used as a forum for interbranch dialogue over Supreme Court cases. When used in this fashion, the dialogue is often focused on cases that challenge congressional power. The results suggest that confirmation hearings are an underappreciated venue for interbranch conversations.